Poetry for us: expressing feelings through creative writing / Nur Ain Syafiqah Zairul Mahsin and Noriah Ismail - Zairul Mahsin, Nur Ain Syafiqah; Ismail, Noriah (Academy of Language Studies, 2023)
There are a lot of websites that exist to help people with their mental health, it's true, but not many of them actually allow people to express their feelings or anything else they want on the website, which is why this one was made. Poetry for Us is a one-for-all website that everyone can use to express their feelings, tell about their days or share anything about themselves. Not everyone has a good support system and someone they can talk to when they are sad, happy, confused, excited, and so on. In fact, many tend to keep their feelings to themselves and let them fade away without telling anyone because they don't have anyone on whom they can rely. So, that is what inspired the author to create this website where everyone can share and express their true feelings via poetry. The website contains a lot of tips on poetry writing. Moreover, they can also read other people’s poems and even better help one another or provide constructive feedbacks on each other’s work. Hence, the website is intended to help people improve their poetry-writing skills because many people enjoy poetry but few know how to write it or the proper technique to write a poem. In addition, the website also offers paid services for poetry reviews, poetry writing and letter writing.